2020
DOI: 10.1111/jgh.15371
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between modified wet suction and dry suction technique for endoscopic ultrasound‐guided fine‐needle biopsy in pancreatic solid lesions

Abstract: Background and Aim Although endoscopic ultrasound‐guided fine‐needle biopsy is widely applied, there is no clear consensus on the optimal biopsy technique. We described a modified wet suction technique (MWEST) with the aim to compare the efficacy and safety between MWEST and the dry suction technique (DST). Methods In this prospective, randomized, crossover, single‐blinded study, patients with suspected pancreatic malignancy were randomized to the DST (group A) or MWEST (group B) for the first pass, and the tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 28 publications
0
28
0
Order By: Relevance
“…Six different suction techniques in EUS-LB have been reported: dry suction, slow pull, wet suction, modified wet suction, wet heparin, and dry heparin. [2][3][4][5] Our technique is close to the wet heparin suction technique and the modified one-pass, one-actuation wet suction technique (EUS-MLB) with some differences. 6 In comparison with the wet heparin suction technique, we left the heparin syringe attached to the proximal port of the needle until just prior to liver puncture.…”
Section: Discussionmentioning
confidence: 96%
“…Six different suction techniques in EUS-LB have been reported: dry suction, slow pull, wet suction, modified wet suction, wet heparin, and dry heparin. [2][3][4][5] Our technique is close to the wet heparin suction technique and the modified one-pass, one-actuation wet suction technique (EUS-MLB) with some differences. 6 In comparison with the wet heparin suction technique, we left the heparin syringe attached to the proximal port of the needle until just prior to liver puncture.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, fine needle biopsy (FNB) could reach higher yields to improve the diagnostic accuracy in pancreatic lesions in a previous study 19. A prospective single-center trial has shown that the wet suction technique could improve the diagnostic rate in FNB for pancreatic solid lesions, compared with dry suction 14. So, the application of combining wet suction and FNB is needed to further investigate in future.…”
Section: Discussionmentioning
confidence: 99%
“…Both of the FNA and FNB are used in obtaining specimens for preclinical model creation, but there is no comparison revealed which one is more suitable. In spite of this, EUS-FNB has been reported to require fewer passes to achieve a conclusive diagnosis, and immunohistochemistry was more successfully performed in FNB samples ( 31 , 45 , 46 ). Additionally, some studies comparing whether the two types of needle can obtain adequate specimen for genomic profiling, yield of DNA, and theranostic potential have revealed that EUS-FNB were considerably superior to EUS-FNA in these aspects ( 27 , 47 ).…”
Section: Characteristics Of Eus-ta Specimens For Establishing Patient...mentioning
confidence: 99%
“…( 25 , 26 ) and endoscopic ultrasound-guided fine-needle biopsy [EUS-FNB; including EchoTip ProCore (Cook Medical), SharkCore (Medtronic), Acquire (Boston Scientific), Sono Tip Topgain (MediGlobe), etc.] ( 25 28 ), could obtain adequate specimens for diagnosis and personalized treatment ( 27 , 29 31 ), with a sensitivity of 86.3–98.4% and a specificity of 100% for the diagnosis of pancreatic malignancy ( 32 ). Furthermore, EUS-TA is generally considered a safe procedure with low morbidity (0.59–0.98%) and mortality (0.02%) rates ( 6 , 33 ).…”
Section: Introductionmentioning
confidence: 99%